Digital Financial Literacy, Fraud Awareness, and Safe Mobile Payment Behavior among Filipino Consumers: The Mediating Role of Perceived Control - Randy A. Cruz Randy A. Cruz; Maria Lourdes Santos Maria Lourdes Santos; Nur Aina Hamzah Nur Aina Hamzah (Kalam Practica Media, 2025)
Digital payments have become ubiquitous in Southeast Asia, yet the expansion of cashless ecosystems has been accompanied by rising fraud attempts, phishing, and social engineering schemes that disproportionately affect consumers with limited digital financial competence. This study examines how digital financial literacy influences safe mobile payment behavior among Filipino consumers, focusing on fraud awareness and perceived control as key psychological mechanisms. Drawing on protection motivation theory, self-efficacy perspectives, and perceived risk logic, the model conceptualizes literacy as a capability that improves threat appraisal, strengthens coping appraisal, and increases the likelihood that consumers adopt safe practices such as verification, device hygiene, and transaction monitoring. Survey data were collected from 644 active mobile payment users across Luzon, Visayas, and Mindanao. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to test direct effects and serial mediation. Results indicate that literacy strengthens fraud awareness and perceived control; awareness increases perceived control by clarifying threats and actionable responses; perceived control strongly predicts safe payment behavior. The findings suggest that anti-fraud outcomes depend not only on awareness campaigns but also on building consumer confidence to execute protective routines. Policy implications emphasize integrating literacy modules into wallet onboarding and community-based education tailored to local fraud narratives.